Bioinspired Artificial Nanodecoys for Hepatitis B Virus. Issue 38 (23rd August 2018) - Liu, Xuan; Yuan, Lunzhi; Zhang, Liang; Mu, Yalin; Li, Xiaoling; Liu, Chao; Lv, Peng; Zhang, Yali; Cheng, Tong; Yuan, Quan; Xia, Ningshao; Chen, Xiaoyuan; et al.
Abstract: A facile route is presented for fabricating a new class of nanomimics that overexpress hepatitis B virus (HBV) receptor by a natural biosynthetic procedure against HBV infection. A nine‐transmembrane HBV‐specific receptor, human sodium taurocholate co‐transporting polypeptide (hNTCP), was engineered to naturally immobilize it onto the cellular surface and subsequently trigger the budding of hNTCP‐anchoring membrane vesicles (hNTCP‐MVs) that favor the HBV virion. hNTCP‐MVs could rapidly block HBV infection in cell models. Furthermore, hNTCP‐MVs treatment could effectively prevent viral infection, spreading, and replication in a human‐liver‐chimeric mouse model of HBV infection. Our findings demonstrate the receptor‐mediated antiviral effect of hNTCP‐MVs to trick HBV and offer novel opportunities for further development of antiviral strategies in nanomedicine. Abstract : Hitting hepatitis : A facile and bioinspired strategy is presented for fabricating a class of nanomimics that over‐express Hepatitis B virus (HBV) receptor by a natural biosynthetic procedure to act against HBV infection.